2021
DOI: 10.1155/2021/6676494
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Bond Performance between Fiber‐Reinforced Polymer Bar and Unsaturated Polyester Resin Concrete

Abstract: Fiber-reinforced polymer (FRP) bar-reinforced unsaturated polyester resin concrete (UPC) can solve the problem of rebar corrosion in ordinary reinforced concrete members. However, it has not been widely used in engineering practice because there have been few studies conducted on the bond behaviors of FRP bar and UPC, and the interaction mechanisms between FRP bar and UPC have not been well understood. A series of pull-out tests are conducted on FRP bar-UPC specimens to study the bond behaviors between these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There are three basic opinions on the influence eter on bond strength. The first of these opinions relies on the concept of th between the core and the fibers on the outer surface (shear lag effect) resu low slip resistance within the epoxy resin and at the epoxy-fiber interface tion of axial tension forces [18][19][20][21] (Figure 2). As the second view, a grea water is assumed to accumulate underneath the FRP bar with increasing The increasing amount of water causes the total volume of gaps in the m crease, which in turn will reduce the FRP-concrete bond strength [22][23][24].…”
Section: Inherent Properties Of Frp Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three basic opinions on the influence eter on bond strength. The first of these opinions relies on the concept of th between the core and the fibers on the outer surface (shear lag effect) resu low slip resistance within the epoxy resin and at the epoxy-fiber interface tion of axial tension forces [18][19][20][21] (Figure 2). As the second view, a grea water is assumed to accumulate underneath the FRP bar with increasing The increasing amount of water causes the total volume of gaps in the m crease, which in turn will reduce the FRP-concrete bond strength [22][23][24].…”
Section: Inherent Properties Of Frp Materialsmentioning
confidence: 99%
“…However, the degree of this reduction is non-linear and dependent on the test parameters. (Figure 7) [18,20,24,78]. The adherence failure types are introduced in Section 3.2.1 with regard to the clear cover and embedment/development length.…”
Section: Development (Ld) or Embedment Length (Le)mentioning
confidence: 99%
“…Moreover, the failure mode and the ultimate bearing capacity of the anchor system are related to the thickness of the anchor agent. W. C. Li et al [33] conducted an experimental study on bond performance between a fiber-reinforced polymer (FRP) bar and unsaturated polyester resin concrete (UPC). It was found that the failure types of FRP bar-UPC specimens depend on the interface bond stress, UPC tensile stress, and stress of the FRP bar; furthermore, the FRP bar-UPC bond strength decreases with the increase of the diameter of the FRP bar due to the shear-lag effect.…”
mentioning
confidence: 99%